The Impact of Universities’ Social Media Content and Digital Brand Equity on Potential Students’ Perception, Engagement and Trust: The case of Egyptian private universities - Shoukry, Mahy (AUC Knowledge Fountain, 2026)
Universities are increasingly using social media platforms as tools for marketing, brand building, and student engagement as a result of the digital transformation in higher education. This study investigates how prospective students' perceptions, levels of engagement, and trust are impacted by universities' digital brand equity and social media content. This study attempts to close the knowledge gap on how visual and user-generated information influences the decision-making processes of potential students, given the competitive environment among Egyptian private institutions. Particular focus is placed on how authenticity, video content, and images influence educational institutions' online appearance and reputation. The methodology used a mixed-approaches strategy that combined survey methodologies with content analysis. In order to classify and evaluate the communication tactics of a few private institutions in Egypt, visual and textual content from their Facebook and Instagram pages was first thoroughly examined. A sample of prospective students was then given a structured online survey to gauge their opinions, involvement, and trust in colleges depending on their exposure to social media. The correlations between the study variables were evaluated using statistical techniques such as regression analysis and hypothesis testing. Data gathered from more than 100 prospective students showed distinct trends connecting students' attitudes and actions with the universities' digital brand equity and the type of social media material they post. The results showed that students' trust and engagement were positively impacted by visually appealing, real, and interactive content. Additionally, students' emotional connection and sense of institutional trustworthiness were greatly improved by the strategic use of video narratives and user-generated content (UGC). These effects were further mitigated by the perceived utility and ease of use of the universities' digital platforms. According to the research, private institutions in Egypt ought to carefully manage their social media presence in order to build their brand equity and strengthen their bonds with potential students. Building trust, improving perceptions, and increasing engagement all depend on content marketing that prioritizes authenticity, interactive participation, and excellent visual storytelling. In addition to adding to the larger scholarly conversation on digital brand equity and higher education marketing tactics in emerging economies, this study provides useful advice for university marketers.